Experimental investigation on the heat transfer of turbulent flow in a pipe oscillating at low frequencies - Gul, H. (Taylor & Francis Inc, 2008)
An experimental study was performed focusing on heat transfer and friction coefficient associated with turbulent oscillating tube flow. For this goal an oscillating mechanism was designed. Experiments were conducted for the low oscillating frequency in the range of 0.008-1.988 Hz and dimensionless amplitude was chosen as X-0 = 0.3, 0.6, and 0.9. Reynolds number was changed from 0.5 x 10(4) to 2.5 x 10(4). The bulk temperature of the fluid at the exit of the oscillating section was fond to be increasing with oscillating frequency and amplitude. For the oscillating cases, heat transfer enhancement is obtained 52% for f = 1.988 s(-1), 40% for f = 1.320 s(-1), and 28% for f = 0.008 s(-1), in comparison with the smooth pipe at the highest Reynolds number. The results also showed that Nusselt number and friction coefficient also increased with increasing frequency and amplitude.
Keywords: oscillating pipe; amplitude; convective heat transfer; experimental study